Automatic Image Dataset Generation for Footwear Detection - Martínez Cesteros, Javier; López Nicolás, Gonzalo (Jornada de Jóvenes Investigadores del I3A, 2019)
In this work, we explore the problem of object detection in the shoe manufacturing application. We propose different methods for the automatic or semi-automatic generation of image datasets. Our approach avoids the time consuming task of collecting labelled images, which is required for training neural networks.